2014
DOI: 10.1007/s11029-014-9454-7
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Analysis of RC Ties Externally Strengthened with FRP Sheets

Abstract: The current study has two objectives: to validate the ability of the Atena finite-element software to estimate the deformations of reinforced concrete (RC) elements strengthened with fiber-reinforced polymer (FRP) sheets and to assess the effect of FRP-to-concrete bond strength on the results of numerical simulation. It is shown that the bond strength has to be selected according to the overall stiffness of the composite element. The numerical results found are corroborated experimentally by tensile tests of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Basically, on top of the epoxy adhesive, the CFRP sheet is mechanically fixed to the concrete by small steel pins. The preliminary numerical analysis using 3D finite element programme [28] demonstrated that the layout of steel pins needs to be properly designed, to avoid stress concentration problem that could risk premature failure. In-depth analysis and investigation taking into account the shearing and bearing resistances of steel pin against concrete, dowel stiffness of steel pin, foundation modulus of concrete, and the group effect of steel pins are recommended.…”
Section: Failure Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, on top of the epoxy adhesive, the CFRP sheet is mechanically fixed to the concrete by small steel pins. The preliminary numerical analysis using 3D finite element programme [28] demonstrated that the layout of steel pins needs to be properly designed, to avoid stress concentration problem that could risk premature failure. In-depth analysis and investigation taking into account the shearing and bearing resistances of steel pin against concrete, dowel stiffness of steel pin, foundation modulus of concrete, and the group effect of steel pins are recommended.…”
Section: Failure Mechanismsmentioning
confidence: 99%
“…The external sheet can be bonded to the concrete surface by constructional adhesive, or additionally fastened mechanically to result in a more effective hybrid jointing [26,27]. As an illustration, Figure 1 demonstrates the efficiency of steel fibres in preventing the formation of splitting cracks in concrete prisms bonded with external carbon fibre-reinforced polymer (CFRP) sheets [28].…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned literature review reveals that the majority of the conducted research is focused on the application of nonconventional jackets in strengthening methods of original RC structural members [17][18][19]21,22,24,[26][27][28][30][31][32][33][34]36,[38][39][40][41][42][43][44][45][48][49][50]56]. Significantly fewer studies investigate such jackets for the repair of preloaded and slightly damaged RC specimens [20,23,25,29,35,37,46,47,[51][52][53][54][55].…”
Section: Research Significancementioning
confidence: 99%
“…These reasons have led researchers to switch to new jacketing techniques with alternative materials such as steel [17][18][19], advanced materials such as fiber reinforced polymer (FRP) [20][21][22][23][24][25], textile reinforced concrete or mortar [26][27][28][29] and shape memory alloys [30][31][32], cement-based materials such as ferrocement [33][34][35][36], steel fibrous concrete or mortar [37][38][39][40], high-performance fiber reinforced concrete [41][42][43][44][45][46][47][48], self-compacting concrete (SCC) [49][50][51][52][53][54], and thin slightly reinforced flowable mortar [55,56]. Many of these jacketing techniques have been proved successful substitutes to common RC jacketing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation